BASIL SEEDS (OCIMUM BASILICUM) EFFICACY IN THE MANAGEMENT OF HYPERLIPIDEMIA. - Norita Irfan1 , Ahmed Bilal2 , Muhammad Arslan Ullah3 , Tabassum Tufail4 , Irfan Ullah5 , Ali Asad Yousaf6, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2022)
ABSTRACT INTRODUCTION: Coronary heart diseases (CHD) are the leading cause of morbidity throughout the World irrespective of gender. CHD can be prevented by proper management of hyperlipidemia in aggregation with healthy diet and lifestyle. OBJECTIVE: The current study was designed to ascertain the effect of basil seeds (Ocimum basilicum) on hyperlipidemia. METHODS: The study was carried out at the University Institute of Diet & Nutrition Sciences, Faculty of Allied Health Sciences, University of Lahore and Major Aziz Bhatti Teaching Hospital (DHQ) Gujrat, Punjab, Pakistan for one year from April, 2021 to April, 2022. Sixty (60) cardiovascular patients from both genders, having cholesterol level ≥ 200 mg/dL were selected and divided into three groups, one group of twenty (20) patients was given no treatment (G0), second group of twenty (20) patients (G1) was given 5.0 g basil seeds per patient per day and third group of twenty (20) patients (G2) was given 10.0 g basil seeds for ninety days. The data was recorded for bio mass index (BMI), total cholesterol (TC) and triglycerides (TG) at 0, 45 and 90 days of study period. RESULTS: Both the doses of basil seeds significantly decreased bio mass index (BMI) from 40.59 to 31.16 (23.22 %), total cholesterol (TC) from 267.77 to 223.64 mg/dl (16.48 %) and triglycerides level (TG) from 250.15 to 207.77 mg/dl (16.94 %) of cardiovascular patients with P value of < 0.001 during the whole span of study. The basil seeds (@ 5.0 and 10.0 g per patient per day significantly reduced bio mass index (BMI), total cholesterol (TC) and triglycerides (TG) of cardiovascular patients during 45 and 90 days. However, the effect of basil seeds was observed sharper in case of 2nd dose i.e. 10.0 g of basil seeds per patient per day. CONCLUSION: Basil seeds have significant effect on lowering bio mass index, total cholesterol and triglycerides levels of cardiovascular patients.